Tracing particle movement for simulation of light history and algal growth in airlift photobioreactors using Positron Emission Particle Tracking (PEPT) - Brighton, Marc (Centre for Bioprocess Engineering Research, 2018)
This Thesis is embargoed. Only the Abstract is available